Compression, tension & lifting stability on a meter gauge flat Wagon: an experimental approach. Issue 4 (8th August 2022) - Das, Apurba; Agarwal, Gopal
ABSTRACT: This paper presents the experimental study of the compression, tension, and lifting stability test on a meter gauge flat wagon. The freight wagon comprises flat body structure and two bogies, where the flat surface is used to transport containers or goods. Two load cells (2000 KN) of HBM Quantum X-MX840 with CATMAN easy software is used for the compression, tension, and lifting stability test. As per EN 12663-2:2010 standard for axial compression test maximum force of 2MN is applied while for diagonal compression test 0.4MN force is applied. The tension test is carried out by applying a maximum tensile load of 1.5 MN while the lifting test is performed with 29T (empty condition) and 57.5T (loaded condition) wagon load. Strain gauges are pasted on identified critical location (based on FEM simulation in ANSYS) of the wagon to capture the strain values. The steady-state strain values are measured and recorded in a data acquisition system. A standard test methodology and the testing setups are established for freight wagon testing. The measured strain values are analyzed for the wagon specific requirements. It is observed that during testing strain values are within the safe zone as per the designed payload for this wagon.